Professionalism of Caregivers as a Pivot to Effective Literacy Skills in Pre- School Classes - Opeyemi Oyewumi , Nasimot; Lawal, Oluwaseun Temitope; Orisadare, Hamdalah Adejoke (CV Media Inti Teknologi, 2025)
This study aims to examine the qualifications of caregivers/teachers as well as the level of professionalism and teaching methods of literacy skills carried out in preschool classes. The study adopted descriptive survey research design. The population comprised all caregivers in private schools in Iwo Local Government, Area of Osun state, Nigeria. The sample consist 3 teachers that were purposively selected from 20 private schools that were randomly selected using simple random sampling technique to make a total number of 60 caregivers. Self - developed questionnaire was used to collect data for the study. Data collected were analyzed using frequency count, percentage, and standard deviation. The results revealed that low percentage 6.7% of caregivers were ECCE certificated, 43.3% had other education disciplines, 46.7% were registered under Teachers Registration Council of Nigeria (TRCN), 52.2% uses the expected methodology for teaching literacy skills while 67.2% were engaged in various professional development and collaborate in teaching literacy skills. It can be concluded that the professionalism of pre-school caregivers/teachers in term of certification is very low, less than 50% were professionally registered but the methodology applied in teaching literacy skills are appropriate. The study recommended that school owners should make recruitment of ECCE professionals a priority and encourage caregivers to engage more in professional development that will equip them in the field of ECCE.